Stagflation in World Economy-Impact on Indian Consumer Market (International Journal of Innovative Research in Engineering & Management, 2021)
Stagflation decimated the global economy throughout the  1970s and early 1980s. Recent empirical analysis suggests that  the 1973 and 1979 oil crises were the catalysts for these high  stagflationary periods. Other issues, such as whether stagflation  is still a concern in the global economy, remain unresolved.  Other than the price of oil, several factors contribute to  stagflation. Humans can see that economies are susceptible to  stagflation in a variety of ways using these measurements.  Furthermore, even though stagflationary events occurred  regularly between 1970 and 2010, the level of stagflation in the  global economy tends to change over time. On the other hand,  if stagflation develops, the magnitude increases. Our findings  imply that stagflation is caused by a complex combination of  factors and that oil price hikes' traditionally large influence has  decreased in the 2000s. Surprisingly, we found evidence that  this impact has grown again at the sample's conclusion. Today's  stagflation, on the other hand, is mostly driven by increasing  interest rates and declining worker productivity. The main  objective of this paper is learn more about Stagflation in World  Economy-Impact on Indian Consumer Market. In the future, the problem is clear since people have been used to comparing  productivity growth year over year or in shorter periods,  typically using aggregates gross national product.
Keywords: Consumer; Economic Growth; Inflation; Market; Stagflation